Enterprise and supplier development as a sustainability construct in mining communities - Mashego, Lesego (University of the Witwatersrand, Johannesburg, 2023)
Sustainability is an integral part of mining in South Africa as the sector grapples with criticism that enough is not being done to support development of mining communities. Enterprise and supplier development (ESD) is one of the ways in which the mining sector contributes to development of businesses operating in the host communities as well as those supplying the operations. These activities are intended to promote entrepreneurship and enable these enterprises to create jobs through provision of support, training, mentorship and funding. This paper investigated whether mining companies’ ESD programmes and the way they are implemented contribute to sustainable enterprises and suppliers in South African mining communities. This was done by analysing content of several reports of mining companies to establish the intention of these companies with respect to establishment of these programmes and the outcomes they are achieving. This was then followed by interviews with beneficiaries of this programmes to gauge whether there is alignment between the companies and the beneficiaries in terms of what constitutes sustainability as well as to determine whether the beneficiaries find value in these activities. With the research questions aimed at accessing thoughts, feelings, experiences and opinions of research participants, the research methodology employed was qualitative. These were then analysed, common themes established and interpretations made around these themes were discussed. A notable finding is that while there is an agreement in terms of what constitutes sustainability, there is a challenge in terms of access to markets – i.e. the exposure and possible exploitation of available supply chain opportunities by these enterprises to enable them to grow
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Mining; Enterprise and supplier development; SMME development; Mining host communities; UCTD; SDG-7: Affordable and clean energy